Septal graft in laryngeal reconstruction - Bahannan, Abdulrahman; Slavíček, Aleš; Taudy, Miloš; Chovanec, Martin (Saudi medical journal, 2006)
A 62-year-old woman presented with symptoms of dyspnea. Ultrasonography and computed tomography examinations revealed mass extending from the cricoid cartilage to the left lobe of thyroid gland and thyroid cartilage. Cytology revealed possibility of cartilaginous origin, which was proven to be chondrosarcoma Grade 1 from the biopsy specimen obtained during panendoscopy. She underwent one stage radical resection and immediate reconstruction of laryngeal skeleton defect by mucocartilaginous graft from the nasal septum. Her postoperative course was optimal with preservation of all the laryngeal functions. Twenty-eight months postoperatively, she had to undergo total laryngectomy as a salvage procedure for the advanced local recurrence. We report on the relatively easy technique for functional reconstruction of the large laryngeal defect with the employment of cartilage graft from the nasal septum.
Keywords: Female; Cartilage; výsledek terapie; ženské pohlaví; Neoplasm Recurrence, Local; biopsie; Nasal Septum; Time Factors; časové faktory; lidé; Laryngeal Neoplasms; laryngektomie; Treatment Outcome; nádory hrtanu; Cricoid Cartilage; Biopsy; nosní přepážka; lokální recidiva nádoru; chondrosarkom; chrupavka; lidé středního věku; Chondrosarcoma; Laryngectomy; Middle Aged; cartilago cricoidea; Humans